An overview of structurally diversified anticonvulsant agents - Al-Otaibi Faisal (Acta Pharmaceutica)
There are several limited approaches to treat epilepsy in hospitals, for example, using medicines, surgery, electrical stimulation and dietary interventions. Despite the availability of all these new and old approaches, seizure is particularly difficult to manage. The quest for new antiepileptic molecules with more specificity and less CNS toxicity continues for medicinal chemists until a new and ideal drug arrives. This review covers new antiseizure molecules of different chemical classes, the exact mode of action of which is still unidentified. Newer agents include sulfonamides, thiadiazoles, semi- and thiosemicarbazones, pyrrolidine-2,5-diones, imidazoles, benzothiazoles and amino acid deriva tives. These new chemical entities can be useful for the design and development of forthcoming antiseizure agents.